Role of Serosal TRPV4-Constituted SOCE Mechanism in Secretagogues-Stimulated Intestinal Epithelial Anion Secretion - Yinghui Cui; Fenglan Chu; Kai Yin; Xiongying Chen; Hanxing Wan; Gang Luo; Hui Dong; Hui Dong; Feng Xu (Frontiers Media S.A., 2021)
As little is known about the role of calcium (Ca2+) signaling mediating the small intestinal epithelial anion secretion, we aimed to study its regulatory role in secretagogue-stimulated duodenal anion secretion and the underlying molecular mechanisms. Therefore, intestinal anion secretion from native mouse duodenal epithelia was examined with Ussing chambers to monitor PGE2-, 5-HT-, and CCh-induced short-circuit currents (Isc). PGE2 (10 μM) and 5-HT (10 μM) induced mouse duodenal Isc, markedly attenuated by serosal Ca2+-free solution and selective blockers of store-operated Ca2+ channels on the serosal side of the duodenum. Furthermore, PGE2- and 5-HT-induced duodenal Isc was also inhibited by ER Ca2+ chelator TPEN. However, dantrolene, a selective blocker of ryanodine receptors, inhibited PGE2-induced duodenal Isc, while LiCl, an inhibitor of IP3 production, inhibited 5-HT-induced Isc. Moreover, duodenal Isc response to the serosal applications of both PGE2 and 5-HT was significantly attenuated in transient receptor potential vanilloid 4 (TRPV4) knockout mice. Finally, mucosal application of carbachol (100 μM) also induced duodenal Isc via selective activation of muscarinic receptors, which was significantly inhibited in serosal Ca2+-free solution but neither in mucosal Ca2+-free solution nor by nifedipine. Therefore, the serosal TRPV4-constituted SOCE mechanism is likely universal for the most common and important secretagogues-induced and Ca2+-dependent intestinal anion secretion. These findings will enhance our knowledge about gastrointestinal (G.I.) epithelial physiology and the associated G.I. diseases, such as diarrhea and constipation.